A High-Precision ID-TIMS U-Pb Dating Method of Apatite - Jiarun TU; Hongying ZHOU; Yurong CUI; Guozhan LI; Jianzhen GENG; Jian ZHANG (Yankuang ceshi)
Apatite belongs to the hexagonal crystal system and has a relatively high (350-550℃) closure temperature, which can accommodate multiple element substitutions into the crystal lattice. It is an important dating mineral for the study of igneous rocks, sedimentary rocks, metamorphic rocks and ore deposits. However, due to the low uranium content and high common lead content of apatite, accurate age determination remains a major challenge for current U-Pb dating techniques. Based on the 208Pb-235U mixed spike, a high-precision isotope dilution-thermal ionization mass spectrometry (ID-TIMS) U-Pb dating method of apatite was established by optimizing the chemical pre-treatment process of sample cleaning, dissolution, and column chromatography separation and purification of U and Pb. The proposed method accurately determined the ages of apatite MAD2 and MAP-3, with 206Pb/238U weighted average ages of 474.6±1.7Ma and 800.7±1.2Ma, respectively. The precision of single-point analysis was better than 0.4%, providing technical support for accurately and precisely dating apatite and development of apatite standards. Moreover, taking MAP-3 as a calibration standard, LA-ICP-MS U-Pb dating was performed on apatite in Durango and Otter Lake, resulting in lower intercept ages of 32.1±0.6Ma (MSWD=1.3, n=36) and 910±13Ma (MSWD=1.6, n=36) in a Tera-Wasserburg diagram, which were consistent with the previous research results within error. This gives further evidence that MAP-3, with extremely low common lead content, is an ideal apatite in situ U-Pb dating standard. Compared with high common lead apatite standards, MAP-3 as an external standard can directly calibrate the isotopic data, effectively simplifying the data analysis process and improving the reliability of in situ apatite U-Pb dating results.